A CONTRASTIVE ANALYSIS BETWEEN BRITISH AND AMERICAN VARIETIES: A CASE-STUDY OF ENGLISH ACCENTS - Sulaiman, Masagus; Yuliani, Sri (JURNAL SMART, 2017)
AbstractThe objectives of thisresearch were to figure out whether or not there were similarites, dissimilarities and possible learning difficulties faced by Indonesian Students inlearning Englishvarieties or accents, as well as its contribution to TEFL. This research useddescriptive-qualitative method. The triangulation technique was used to collect the data, andto analyze the data, the researchers useddescriptive analysis(i.e. identifying, classifying, interpreting, predicting and drawing conclusions).The results showed that British and American varieties had two similaritieson meanings and word functions and four dissimilarities on diction, spelling, grammar and pronunciation.Keywords: British, American, Varieties, Accents.